Topeng Surakarta as a Source of Ideas for Batik Motif Design in Women's Casual Clothes - Kristanti Kristanti; FP Sri Wuryani (Universitas Indraprasta PGRI, 2020)
Indonesia is a country that has a diverse form of arts and cultures, one of which is the art of mask that grows and develops in various regions. Masks in a broad sense vary greatly from shape, function, and materials for which they are made. The need for the use of masks is often found in artistic, ritual, religious, health, and performance activities. The tradition of mask in Indonesia has existed since before the history of writing. Masks are believed to represent the spirits of the deceased and are often decorated with human and animal forms to symbolize the supernatural world and the relationship between humans and their origins. This paper explored the form of mask, specifically the Surakarta mask as a source of idea in batik motif creation. The batik motif was made by stylization of the mask using remasol dye and colet technique, resulting in five batik clothes that are cut and sewn into women casual clothes. By turning Surakarta mask batik motif into casual clothing, the clothes made can introduce the art of mask in Surakarta to the wider community, preserving both the art of mask and the art of batik as a high value tradition full of local wisdom.